PENGARUH KONSELING KESEHATAN TERHADAP KEPATUHAN PASIEN DALAM PENGOBATAN TBC DI PUSKESMAS SUMBANG I DAN II KABUPATEN BANYUMAS - Martyarini Budi Setyawati (Viva Medika, 2012)
Adherence to anti tuberculosis drug is important factor for patientsrecovery. Its is needed the strategy by counselling method that directly andintensively to patient, in order to patient can direct counselling and consultancywith health officer so the patient can abtaining information about TBC‟s disease and capablechange toward positive behavior for increasing medication efficacy byconsuming the combination drugs and routine control to Puskesmas. Thepurpose of this study especially to investigate the effect of healthcouncellingmethod on patients adherence to anti tuberculosis drug at Puskesmas Sumbang Iand II Kabupaten Banyumas Tahun 2013. The method of this study was preexperimental design by pre-test and post-test group approach to10 responder.Subject was chosen by total sampling. The result showed, most of responderbecame obey in consuming the combination drugs and control to the Regional‟s Publict Health. Based on the result, the statistic test of Mc Nemar showed the p value = 0,008 (< 0,05), its mean Ha had been accepted. This matter showed that there were effect of health councelling method on patients adherence to antituberculosis drug. Because of that, Regional‟s Publict Health is very necessary toprovide the facility to increase health councelling service. Keyword : Health Councelling, Adherence, Medication of TBC